Case Report: Bosentan and Sildenafil Exposure in Human Milk - A Contribution From the ConcePTION Project - Nauwelaerts, Nina; Ceulemans, Michael; Deferm, Neel; Eerdekens, An; Lammens, Bart; Armoudjian, Yeghig; Van Calsteren, Kristel; Allegaert, Karel; de Vries, Loes; Annaert, Pieter; Smits, Anne (Frontiers in Pharmacology, 2022)
Introduction: Quantitative information on disposition of maternal medicines in human milk remains a major knowledge gap. This case report presents the clinical and pharmacokinetic data of a single mother-infant pair exposed to bosentan and sildenafil for the treatment of pulmonary arterial hypertension (PAH) during lactation. Case presentation: A 43-year old mother was treated with sildenafil (20 mg, 3x/day) and bosentan (125 mg, 2x/day) for PAH. Her 21-months old infant received breastfeeding in combination with adequate complementary foods. Milk samples were collected over 24 hours, at day 637 and 651 after delivery. The observed average steady-state concentrations of sildenafil (2.84 µg/L) and bosentan (49.0 µg/L) in human milk were low. The Daily Infant Dosage ingested by the nursing infant through human milk was 0.02 µg/kg/day for sildenafil and 0.29 µg/kg/day for bosentan at day 637, and 0.03 µg/kg/day and 0.60 µg/kg/day at day 651. The Relative Infant Dose calculated for an exclusively breastfed infant with an estimated milk intake of 150 mL/kg/day, was 0.06% for sildenafil and 0.24% for bosentan. General health outcome of the infant, reported by the mother, was uneventful until the sampling days. Conclusion: Low medicine concentrations were found in human milk expressed 21 months after delivery after maternal intake of 20 mg sildenafil three times daily and 125 mg bosentan twice daily. General health of the nursing infant until sampling was reported as optimal by the mother.